Moss antheridia are desiccation tolerant: Rehydration dynamics influence sperm release in Bryum argenteum. Issue 5 (10th May 2016) - Stark, Lloyd R.; McLetchie, D. Nicholas; Greenwood, Joshua L.; Eppley, Sarah M.
Abstract : PREMISE OF THE STUDY: Free‐living sperm of mosses are known to be partially desiccation tolerant. We hypothesized that mature moss antheridia should also tolerate desiccation and that rehydration to partial turgor (prehydration) or rehydration to full turgor (rehydration) before immersion in water is required for full recovery from any damaging effects of prior desiccation. METHODS: Bryum argenteum (silvery‐thread moss) was grown in continuous culture for several months, produced mature perigonia (clusters of antheridia), and these were subjected to a slow rate of drying (∼36 h from full turgor to desiccation) and equilibration with 50% relative humidity. Perigonia were prehydrated (exposed to a saturated atmosphere) or rehydrated (planted upright in saturated media) for 0, 45, 90, 135, 180, and 1440 min, then immersed in sterile water. Time to first sperm mass release, number of antheridia releasing sperm masses, and the integrity of the first sperm mass released were assessed. KEY RESULTS: Rehydration of dried antheridia for at least 3 h before immersion in water resulted in antheridia functioning similar to control undried antheridia. Compared with rehydration, prehydration was not effective in the recovery of antheridia from desiccation. CONCLUSIONS: For the first time, moss antheridia are shown to be fully desiccation tolerant at a functional level, capable of releasing fully functional sperm following a slow drying event provided the antheridia are allowed to rehydrate at least 3 h before immersion in water.